Consciousness: A Very Short Introduction - Blackmore, Susan (New York Oxford University Press, 2005)
How can a physical brain create our experience of the world? What creates our identity? Do we really have free will? Could consciousness itself be an illusion? This book attempts to clarify the potentially confusing arguments, and the major theories using illustrations, cartoons, and experiments.
Includes Index and Illustrations.
Keywords: Art, Modern